Mitoprotective Effects of a Synergistic Nutraceutical Combination: Basis for a Prevention Strategy Against Alzheimer’s Disease - Jayatunga, Dona P. W.; Hone, Eugene; Fernando, W. M. A. D. Binosha; Garg, Manohar L.; Verdile, Giuseppe; Martins, Ralph N. (Frontiers in Aging Neuroscience, 2022)
Evidence to date suggests the consumption of food rich in bioactive compounds such as polyphenols, flavonoids, omega-3 fatty acids may potentially minimize age-related cognitive decline. For neurodegenerative diseases such as Alzheimer’s disease (AD), which do not yet have definitive treatments, the focus has shifted towards using alternative approaches, including prevention strategies rather than disease reversal. In this aspect, certain nutraceuticals have become promising compounds due to their neuroprotective properties. Moreover, the multifaceted AD pathophysiology encourages the use of multiple bioactive components that may be synergistic in their protective roles when combined. The objective of the present study was to determine mechanisms of action underlying the inhibition of Aβ1-42-induced toxicity by a previously determined, three-compound nutraceutical combination D5L5U5 for AD. In vitro experiments were carried out in human neuroblastoma BE(2)-M17 cells for levels of ROS, ATP mitophagy, and mitobiogenesis. The component compounds luteolin (LUT), DHA, and urolithin A (UA) were independently protective of mitochondria; however, the D5L5U5 preceded its single constituents in all assays used. Overall, it indicated that D5L5U5 had potent inhibitory effects against Aβ1-42-induced toxicity through protecting mitochondria. These mitoprotective activities included minimizing oxidative stress, increasing ATP and inducing mitophagy and mitobiogenesis. However, this synergistic nutraceutical combination warrants further investigations in other in vitro and in vivo AD models to confirm its potential to be used as a preventative therapy for AD.